Human rights and socio-economic transformation in South Africa - Ngang, Carol C. (Human rights review, 2021)
In this article, I revisit the question of socio-economic transformation in South Africa to illustrate how it connects with human rights, essentially because, as I argue, transformation is unattainable without a comprehensive understanding of the central role of human rights in activating that process. I state the claim that the progressive human rights culture on the basis of which South Africa launched itself from the demise of apartheid into one of the most treasured constitutional democracies globally is noticeably disintegrating, displaying signs of post-independence failures that have bedevilled many other African countries. It leaves unanswered questions with regard to the transitional promise for a better life and equitable opportunities. Not only is the political intent to actualise the project for socio-economic transformation apparently lacking, prospects that the expectations of the impoverished segments of the population may never be fulfilled prompts the need for an in-depth diagnosis of the contrasts that dissociate the country from its constitutional commitment to remedy the injustices of the past, which remain visible in legislation, policies, institutional practices, governance mechanisms and social perceptions that seem to be hardwired to accommodate transformation. I aim to demonstrate that even though South Africa’s constitutional democracy is anchored on a radical undertaking to eradicate the injustices that unreasonably limit options for the larger part of the population, there is no genuine adherence to the constitutional standards for transformation under the present dispensation, which is shaped by misconceived and misdirected priorities at the expense of human rights that lie at the core of the project for socio-economic transformation. I articulate these viewpoints by bringing into sharper focus the connection between human rights and transformation so that perhaps, the arguments may provide conceptual direction in academic discourses and probably also shape policy direction in crafting transformative solutions to the socio-economic exigencies that South Africa is confronted with.